2018
DOI: 10.1158/1078-0432.ccr-18-1542
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of EGFR-Dependent and -Independent Resistance Mechanisms to Osimertinib and Continuation Therapy Beyond Progression in EGFR-Mutant NSCLC

Abstract: Osimertinib was initially approved for T790M-positive non-small cell lung cancer (NSCLC) and, more recently, for first-line treatment of -mutant NSCLC. However, resistance mechanisms to osimertinib have been incompletely described. Using cohorts from The University of Texas MD Anderson Lung Cancer Moonshot GEMINI and Moffitt Cancer Center lung cancer databases, we collected clinical data for patients treated with osimertinib. Molecular profiling analysis was performed at the time of progression in a subset of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
316
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(334 citation statements)
references
References 35 publications
10
316
0
1
Order By: Relevance
“…In our patient cohort, we detected the previously reported, and likely resistance‐associated changes, BRAF V600E and PIK3CA using plasma NGS. We have not detected other secondary EGFR mutations such as C797 and L792 or C‐MET amplification which were reported to be present in 26% and 14% of cases respectively likely due to the sample size. There were four cases of acquired TP53 mutations at the time of osimertinib resistance, with patient 3 reaching a very high allelic frequency of 24% (Table ).…”
Section: Discussionmentioning
confidence: 56%
“…In our patient cohort, we detected the previously reported, and likely resistance‐associated changes, BRAF V600E and PIK3CA using plasma NGS. We have not detected other secondary EGFR mutations such as C797 and L792 or C‐MET amplification which were reported to be present in 26% and 14% of cases respectively likely due to the sample size. There were four cases of acquired TP53 mutations at the time of osimertinib resistance, with patient 3 reaching a very high allelic frequency of 24% (Table ).…”
Section: Discussionmentioning
confidence: 56%
“…EGFR-mutated NSCLCs are routinely and effectively treated with EGFR TKIs, but resistance inevitably develops via characteristic mechanisms including secondary EGFR resistance mutations (i.e. T790M) and, notably, EMT 68 . Thus, we evaluated expression of ACE2 in EGFR-mutated NSCLC cells (HCC4006 and HCC827) treated with the EGFR TKI erlotinib until resistance occurred 69 .…”
Section: Alternative Emt Repression Of Ace2 Via Egfrmentioning
confidence: 99%
“…Gene amplification of ERBB2, MET, MDM2 or CDK4 alone leads to poor prognosis for NSCLC regardless of EGFR gene mutation (25)(26)(27). Furthermore, Le et al (11) and Blakely et al (14) reported that cell cycle gene alteration, such as CDK4 or CDK6, shortens PFS following osimertinib therapy. Patients with EGFR mutant NSCLC accompanied by TP53 mutation, ERBB2 amplification, or MET amplification before first-or second-generation EGFR-TKI treatment exhibited a shorter time to progression and also showed resistance to third-generation EGFR-TKIs (12,13,28).…”
Section: Discussionmentioning
confidence: 99%
“…Several other mechanisms of resistance against all generation EGFR-TKIs have been identified including tertiary gene mutations other than EGFR C797S mutation (9)(10)(11), activation of bypass signaling by gene amplification (e.g., ERBB2 (12) and MET (13,14), driver gene mutations (e.g., RAS, RAF and PIK3CA) (3,15), gene alteration in cell cycle genes (14), and transformation to mesenchyme, small cell carcinoma (SCC), or squamous cell carcinoma (SqCC) (2,16,17). These described EGFR-TKI resistance mechanisms may also be expressed during the pre-TKI NSCLC state (6,15) and can be a challenge for cancer treatment of NSCLC patients with EGFR mutations.…”
Section: Introductionmentioning
confidence: 99%